Potential step chronoamperometry at hemispherical mercury electrodes: The formation of thallium amalgams and the measurement of the diffusion coefficient of thallium in mercury - Limon-Petersen, J; Rees, N; Streeter, I; Molina, A; Compton, R (2008)
Results for the measurement of the diffusion coefficients of Tl0 in a Tl/Hg amalgam (DHg), and Tl+ in 1.0 M KF aqueous solution (Daq) are presented. The values of DHg = (1.2 ± 0.1) × 10-5 cm2 s-1 and Daq = (2.4 ± 0.2) × 10-5 cm2 s-1 at 22 ± 1 °C are obtained by means of comparison of experimental deposition and stripping chronoamperometric transients with theoretical simulations for a 12.5 μm radius hemispherical mercury drop in which Tl is first deposited and then stripped. © 2008 Elsevier B.V. All rights reserved.